Quality Improvement, Quality Assurance, and Benchmarking: Comparing two frameworks for managing quality processes in open and distance learning - Inglis, Alistair (International Review of Research in Open and Distributed Learning, 2005)
Managing quality processes become critically important for higher education institutions generally, but especially for institutions involved in open and distance learning. In Australia, managers of centers responsible for open and distance learning have identified two frameworks that potentially offer ways of conceiving of the application of quality processes: the Quality Framework published in Inglis, Ling, and Joosten (1999); and the Benchmarking Framework published in McKinnon, Walker, and Davis (2000). However, managers who have been considering applying one or other framework within their institutional contexts have had to face the issue of how they should choose between, or combine the use, of these frameworks. Part of their dilemma lies in distinguishing among the related functions of quality improvement, quality assurance, and benchmarking. This article compares the frameworks in terms of their scope, institutional application, structures, and method of application, and then considers what implications the similarities and differences between the frameworks have for their use.